Safety of Robot‐Assisted Radical Cystectomy for Muscle‐Invasive Bladder Cancer: A Real‐World Analysis Using the National Clinical Database in Japan - Shingo Hatakeyama; Hiroyuki Yamamoto; Hiroshi Kitamura; Toshiyuki Kamoto; Eiji Kikuchi (Cancer Medicine)
ABSTRACT Background Radical cystectomy (RC) is a standard‐of‐care treatment for muscle‐invasive bladder cancer (MIBC). However, there is a lack of data comparing the benefit of robot‐assisted radical cystectomy (RARC) with laparoscopic radical cystectomy (LRC) or open radical cystectomy (ORC) in Japan. We aimed to explore the safety of RARC compared with that of LRC or ORC using the Japanese National Clinical Database (NCD). Methods This retrospective study reviewed the data of 17,549 patients with MIBC who underwent radical cystectomy between February 2019 and December 2022 in the Japanese NCD. We compared the postoperative complications within 30 days between the surgical procedures using the Clavien–Dindo classification. Multivariable logistic regression analysis was conducted for grade ≥ 3 postoperative complications. Results Overall, 8308, 3101, and 6140 patients underwent RARC, LRC, and ORC, respectively. The rates of any grade and grade ≥ 3 postoperative complications within 30 days were significantly lower in the RARC group than in the ORC group. RARC had no significant difference in grade ≥ 3 postoperative complications in the ileal neobladder. Regarding any grade postoperative complications, RARC had a significantly lower rate of delirium, surgical site infection, sepsis, and gastrointestinal tract leakage than ORC. Multivariable logistic regression analysis revealed that the incidence of grade ≥ 3 postoperative complications was significantly lower in RARC (odds ratio, 0.83; 95% confidence interval, 0.72–0.95). Conclusions RARC had a lower complication rate compared with ORC. LRC had comparable outcomes to RARC. The findings of this study contribute to RARC as being the standard treatment for MIBC.